2007
DOI: 10.1016/j.rapm.2006.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Salivary α-Amylase Activity and Pain Scale in Patients With Chronic Pain

Abstract: Because there was a significant correlation between VAS pain scale and salivary alpha-amylase, we suggest that this biomarker may be a good index for the objective assessment of pain intensity. In addition, a simple to use portable analyzer may be useful for such assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
46
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 14 publications
8
46
3
Order By: Relevance
“…These results are similar to those reported previously by Shirasaki and Motamayel [4,5]. It has been reported that psychological stress activates the SAM system [6].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results are similar to those reported previously by Shirasaki and Motamayel [4,5]. It has been reported that psychological stress activates the SAM system [6].…”
Section: Discussionsupporting
confidence: 93%
“…Shirasaki found good correlation between scales of pain intensity and SAA. This is because painful stimuli activate the sympathetic-adrenal medullary (SAM) system and hypothalamic-pituitary-adrenal (HPA) axis [4]. Some children need their primary teeth to be extracted under local anesthetic injection during the exfoliation period.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the observation that pentazocine, but not midazolam, effectively reduced the high sAMY level as well as the body motion indicates that the stress shown by sAMY in a patient under DS is physiological stress; namely, excitation of the sympathetic nervous system caused by pain stimuli, rather than psychological stress. The sAMY has previously been reported to be useful for assessing pain in patients suffering from chronic low back or leg pain [20]. However, that report showed the sAMY to be related to the self-assessment of pain in a patient who was aware.…”
Section: Discussionmentioning
confidence: 92%
“…46 Recent evidence suggests that sAA may represent an objective neuroendocrine measure for changes in affect and pain intensity. [39][40][41][42] Because reflexology seems to be of clinical usefulness for reducing distress, further clinical and laboratory studies into the mechanisms by which reflexology acts upon the sympathetic nervous system are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…[38][39] sAA possesses diurnal qualities, that is, levels shift through the course of the day. [40][41][42] Thus, saliva samples (of 0.5-1.0 mL volume each) were collected in subjects within 30 minutes of awakening and every 3 hours thereafter (midmorning, early afternoon and late afternoon) to capture the circadian pattern. On each day, the collection procedures was identical.…”
Section: Study Outcomesmentioning
confidence: 99%